Anterior composite restorations: A systematic review on long-term survival and reasons for failure. Issue 10 (October 2015) - Demarco, Flávio F.; Collares, Kauê; Coelho-de-Souza, Fabio H.; Correa, Marcos B.; Cenci, Maximiliano S.; Moraes, Rafael R.; Opdam, Niek J.M.
Abstract Objective In this study the literature was systematically reviewed to investigate the clinical longevity of anterior composite restorations. Data Clinical studies investigating the survival of anterior light-cured composite restorations with at least three years of follow-up were screened and main reasons associated with restoration failure were registered. Sources PubMed, Scopus, and Cochrane databases were searched without restriction on date or language. Reference lists of eligible studies were hand-searched. The grey literature search was not made systematically. Study selection Two reviewers screened titles and/or abstracts of 2273 unique studies. In total, 41 studies were selected for full-text reading, from which 17 were included in the qualitative synthesis. The included studies evaluated the clinical performance of Class III and/or IV restorations (10 studies), which were placed due to caries, fracture, or replaced old restorations; veneers and full-coverage restorations placed for aesthetic reasons (five studies); and restorations in worn teeth (two studies). Annual failure rates (AFRs) were calculated for each study. Conclusions In total, 1821 restorations were evaluated and the total failure rate was 24.1%. AFRs varied from 0 to 4.1% and survival rates varied from 53.4% to 100%. Class III restorations generally had lower AFRs than the other restorations. Few studies addressed factors associated with failure, which included adhesive technique, composite resin, retreatment risk, and time required to build-up the restoration. Fracture of tooth/restoration was the most common reason for failure, whereas failures related to aesthetic qualities (color, anatomical form, surface stain) were more frequent when restorations were placed for aesthetic reasons.